IDEAL SISTEM HUKUM DALAM PENGARUH POLITIK DI INDONESIA: Oktir Nebi - Nebi, Oktir (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
The distrust of the legal system in Indonesia, which is becoming more and more concerning, is a trend that occurs not only in judicial institutions but also in all social strata. The influence of the product of legislation by a political institution which is strongly influenced by the great political forces in political institutions. Actors of legal politics are tools of government in a broad sense, namely tools of government in the legislative field, and tools of government in the judiciary.